TINJAUAN SUBJEK HUKUM TINDAK PIDANA KHALWAT DALAM QANUN NO. 14 TAHUN 2003 - Fadli Ibrahim (Syarah: Jurnal Hukum Islam & Ekonomi, 2019)
Seclusion with the opposite sex is an act that violates Islamic law, but this isconsidered commonplace among young people now. They consider it to beordinary and trendy behavior today. Exaggeration and conversations withthe opposite sex are considered normal without considering the effectscaused by the behavior, so the rampant practice of khalwat violations isrampant everywhere, even the unfortunate thing is that the perpetrators areunderage children which gives rise to an assumption of how aspects the lawfor handling khalwat cases in Qanun number 14 of 2003 which has beenarranged in such a way and how the provisions of the subject of khalwat lawaccording to Qanun No. 14 of 2003. After further investigation, it wasobtained, firstly the legal aspects contained in Qanun No. 14 of 2003included the definition of khalwat article 1, the participation of thecommunity in prevention and prevention, namely articles 8, 9, 10, 11 and 12,supervision and guidance, namely articles 13, 14 and 15, investigations andprosecutions, namely articles 16, 17, 18, 19, 20 and 21, the provisions of'uqubat are articles 22, 23, 24 and 25, and the implementation of' uqubatagainst the perpetrators, namely article 26, 27, 28, 29 and 30. Second, thesubject of khalwat law in Qanun No. 14 of 2003 is not specifically andspecifically regulated, if those who do it are adults, it will be processed inaccordance with applicable regulations, but if those who do it are underageadolescents, hence there is a legal obscurity here, so that the parties runningthe field only provide mentoring and mental rehabilitation, this is due to theabsence of provisions that can be used as a basis for law enforcement. umagainst the perpetrators of khalwat by underage adolescents, and this is alegal imbalance in the implementation on the ground by the WilayatulHisbah. Therefore, it is necessary to review the qanun, so that deficienciescan be improved.